Numerical analysis of discharge gap related fluctuations in a cylindrical positive discharge corona - Kamran Abu Talib; Muhammad Yasin Naz; Ahmed Ahmed Ibrahim; Kashif Kamran; Muhammad Ayyaz; Muhammad Shoaib (AIP Advances, 2024)
An efficient technique was used to model corona discharges without incorporating flux corrections. A position-state separation (POSS) technique was employed to solve the convection-dominated continuity equations prevalent in designing efficient corona discharges. The suggested approach utilizes an Eulerian scheme to solve the convective acceleration, diffusion, and response subproblems. The exceptional performance of POSS in terms of computing cost, resilience, and resolution is demonstrated by a series of numerical tests in various dimensions and coordinate systems. MATLAB was used to run four tests, namely, the square test, Davies test, general advection-diffusion test, and corona test. The average error in POSS was calculated as 0.06, which is much lower than the error in FEM-FCT (0.2677) and FVM-MUSCL (0.2650) algorithms. A 1 mm thick peak of space charge was formed around the anode after 1.2 ns. For an outer radius of 2 cm, ripples in ionizing waves were seen at t = 5000 ns. All the ionizing peaks were produced at around 0.5 cm away from the anode.